2017
DOI: 10.1093/nar/gkx508
|View full text |Cite
|
Sign up to set email alerts
|

Autoregulation of RBM10 and cross-regulation of RBM10/RBM5 via alternative splicing-coupled nonsense-mediated decay

Abstract: Mutations in the spliceosomal RNA binding protein RBM10 cause TARP syndrome and are frequently observed in lung adenocarcinoma (LUAD). We have previously shown that RBM10 enhances exon skipping of its target genes, including its paralog RBM5. Here, we report that RBM10 negatively regulates its own mRNA and protein expression and that of RBM5 by promoting alternative splicing-coupled nonsense-mediated mRNA decay (AS-NMD). Through computational analysis and experimental validation, we identified RBM10-promoted s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
75
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(77 citation statements)
references
References 76 publications
0
75
0
2
Order By: Relevance
“…For instance, RBM10 is involved in the alternative splicing of pre‐mRNA from NUMB , FAS , Dlg4 , and SMN2 . RBM10 has even been shown to promote alternative splicing‐coupled nonsense‐mediated mRNA decay (AS‐NMD) of its own pre‐mRNA and that of RBM5 . The interaction of RBM10 with components of spliceosomal complexes also supports a role for RBM10 as a regulator of alternative splicing …”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…For instance, RBM10 is involved in the alternative splicing of pre‐mRNA from NUMB , FAS , Dlg4 , and SMN2 . RBM10 has even been shown to promote alternative splicing‐coupled nonsense‐mediated mRNA decay (AS‐NMD) of its own pre‐mRNA and that of RBM5 . The interaction of RBM10 with components of spliceosomal complexes also supports a role for RBM10 as a regulator of alternative splicing …”
Section: Introductionmentioning
confidence: 91%
“…For instance, both positive and negative expression correlations have been noted: (1) in HEK293 human embryonic kidney cells, RBM10 overexpression correlated with increased RBM5 exon 6 exclusion and overall decreased RBM5 mRNA levels, whereas RBM10 knockdown correlated with a slight decrease in RBM5 exon 6 exclusion and overall higher RBM5 mRNA expression levels; (2) in SHSY5Y human neuronal cells, RBM10 knockdown correlated with increased levels of RBM5 protein; (3) in H9c2 rat myoblast cells, RBM5 knockdown correlated with decreased RBM10 mRNA expression; and (4) in GLC20 RBM5 ‐null small cell lung cancer cells, increased RBM5 expression correlated with increased protein expression of specific RBM10 splice variants . Of note, the first and fourth study described not only showed a correlation between RBM5 and RBM10 expression, but also direct interactions between them: (1) in HEK293 cells, RBM10 bound the RBM5 intron 5 5′‐splice site and intron 6 3′‐splice site, influencing RBM5 alternative splicing and ultimately leading to RBM5 AS‐NMD; and (2) in GLC20 cells, RBM5 bound only one specific RBM10 splice variant, and was associated with increased protein expression of RBM10v2 . Considered together, these results demonstrate that relationships between RBM5 and RBM10 occur across cell types and species, highlighting their potential fundamental importance to the cell.…”
Section: Regulation Of Rbm10mentioning
confidence: 99%
“…Examples include hnRNPL/hnRNPLL [30], PTBP1/PTBP2 [36,42], RBM10/ RBM5 [39], 67 RBFOX2/PTBP2 [43], RBFOX2/RBFOX3 [44] and others (see [45] for the detailed analysis of cross-68 regulatory networks). Disruption of auto-or cross-regulation of SFs is associated with human pathogenic 69 states, including neurodegenerative diseases and cancer [39,[46][47][48]. 70 The connection between AS event and the position of PTC that is induced by it is not always evident 71 because PTC may appear anywhere downstream of the frameshift.…”
mentioning
confidence: 99%
“…36 It has been increasingly reported over past years that NMD is not only dedicated to the destruction of 37 PTC-containing mRNAs that appear as a result of nonsense mutations or splicing errors, but that it also 38 plays a key role in regulating the expression of a broad class of physiological transcripts [7,8]. Targets of 39 NMD include tissue-specific transcripts [9], transcripts with mutually exclusive exons [10], mRNAs with 40 upstream open reading frames (uORFs) and long 3'-untranslated regions (UTRs) [11], and transcripts 41 emanating from transposons and retroviruses [12]. The mechanism, in which the cell employs alternative 42 splicing (AS) coupled with NMD to downregulate the abundance of mRNA transcripts, shortly termed 43 AS-NMD [13] (also referred to as regulated unproductive splicing and translation [7] or unproductive 44 splicing [14]), is found in all eukaryotes that have been studied to date and often exhibits a high degree of 45 evolutionary conservation [15,16].…”
mentioning
confidence: 99%
See 1 more Smart Citation